2010
DOI: 10.1177/0160323x10364747
|View full text |Cite
|
Sign up to set email alerts
|

Tenure in Office of Big City Mayors

Abstract: In this study of tenure in office, tenure is measured by both the number of years and the number of terms served by 848 mayors of nineteen major American cities who held office between 1820 and 1995. An examination of this data finds that mayoral tenure has increased substantially when measured by the years served but only marginally when measured by the number of terms served. A multivariate analysis of mayors serving between 1853 and 1995 supports Fiorina’s contention that performance in office is related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Chief among them is work experience, encompassing life events occurring in and perceptions gained in a work setting. 6 With the growing median age of U.S. workers (Toossi, 2015), the experience of employees in executive leadership, middle management, and line staff positions has been studied across public and private sector settings (Allen & Panian 1982;Eitzen & Yetman 1972;Finkelstein & Hambrick 1990;Fizel & D'Itri 1997;Henderson et al 2006;Juenke 2005;Marato & Rodgers 1984;McEnrue 1988;McNitt 2010;Miller & Shamsie 2001;Mondak 1995;Scully 1994;Taylor & Greve 2006;Thurmond 2010). Theories of work experience have advanced from narrow early conceptualizations to the more complex, nuanced and multi-dimensional definitions and approaches.…”
Section: Managerial Tenure and Performancementioning
confidence: 99%
“…Chief among them is work experience, encompassing life events occurring in and perceptions gained in a work setting. 6 With the growing median age of U.S. workers (Toossi, 2015), the experience of employees in executive leadership, middle management, and line staff positions has been studied across public and private sector settings (Allen & Panian 1982;Eitzen & Yetman 1972;Finkelstein & Hambrick 1990;Fizel & D'Itri 1997;Henderson et al 2006;Juenke 2005;Marato & Rodgers 1984;McEnrue 1988;McNitt 2010;Miller & Shamsie 2001;Mondak 1995;Scully 1994;Taylor & Greve 2006;Thurmond 2010). Theories of work experience have advanced from narrow early conceptualizations to the more complex, nuanced and multi-dimensional definitions and approaches.…”
Section: Managerial Tenure and Performancementioning
confidence: 99%
“…These municipalities will tend to have “district elections and mayoral control of administration,” which offer, “a more politicized system that is more vulnerable to [electoral] demands” (Sharp , 17). The full‐time nature of elective office, which is often a feature of mayor‐council governments, requires incumbents to be sensitive to electoral pressures (McNitt ). The rules and norms that define governing institutions can provide powerful inducements that encourage and discourage all types of behavior (March and Olsen ).…”
Section: Local Government Designmentioning
confidence: 99%
“…In a study that investigated government structures in cities, French () found that city managers and CAOs in council‐manager municipalities focused a majority of their time on management issues. As for the elected officials in mayor‐council cities, McNitt () makes the case that they are more responsive to voters because the form of government incentivizes the official’s behavior of promoting the incumbents’ personal and political goals to ensure reelection. Further, popularly elected mayors’ decisions are limited by their campaign promises and the need to be reelected (McNitt ; Svara ).…”
Section: Local Government Designmentioning
confidence: 99%
“…Murphy (1980), on the other hand, argues that mayors tend to perform at similar levels to those coming from other "stepping-stone" offices-particularly state legislators. 1 Moreover, he contends that the mayoralty is frequently the culmination of a political career, a point supported by other research (McNitt 2010). While all of these studies represent informative starting points-and yield important insights into separate research questions-they almost exclusively focus on a narrow subset of the nation's largest cities.…”
Section: Introductionmentioning
confidence: 99%
“…Bledsoe's (1993) study of city councillors, however, reveals that state legislative seats tended to be better routes for career advancement than the mayoralty.2 For example, althoughMcNitt's (2010) data includes 848 mayors, he only studies 19 "major American cities" longitudinally.…”
mentioning
confidence: 99%